EFFECT OF SERUM PROLACTIN ON FERTILITY- A CASE REPORT - DR.S.V.MYTHILI; DR.T.VIDHYA LOGINI (International Journal of Pharma and Bio Sciences, 2014)
Hyperprolactinaemia is the presence of abnormally high levels of prolactin in the blood. Normal levels are less than 20 ng/mL for women, and less than 450 mIU/L for men. A prolactinoma is a benign tumor (adenoma) of the pituitary gland that produces a hormone called prolactin. It is the most common type of pituitary tumor. Hyperprolacinemia is a cause for infertility which is reversible with treatment with dopamine agonists.